Faktor-Faktor Yang Mempengaruhi Siklus Menstruasi pada mahasiswi di Universitas Pasir Pengaraian - ., Andriana; Aldriana, Nana; ., Andria (Jurnal Martenity and Neonatal, 2018)
Normal menstrual cycle occurs around 24-32 days, whereas in abnormal menstrual cycle is less than 24 days and more than 32 days. Menstrual cycle abnormalities indicate an impaired function of the reproductive system such as ovarian cysts, and endometritis. Factors that cause reproductive system disorders such as menstrual cycles include hormonal disorders, stress, systemic disorders, thyroid, excessive prolactin hormone, high or low BMI, nutritional status, physical activity, and menarche age. The purpose of this study is to determine the factors that affect the menstrual cycle. This research type is research with analytical survey design with cross sectional approach. The sampling technique is by simple random sampling.From the results of this study, it can be seen that the respondents at the University of Sand Pengaraian with the most menarche age at age 12-14 years (69.8%), Body Mass Index (IMT) at most on normal BMI (66%), and for activities physical, most respondents do physical exercise less 3 times a week (92,5), and menstrual cycle at most is normal menstrual cycle (60,4%). Based on the results of this study, it can be concluded that there is a significant relationship between menarche age and body mass index with menstrual cycle, but there is no significant relationship of physical activity with menstrual cycle. It is recommended for young women to understand their menstrual cycle as an indicator of female reproductive health.